Summary of the 10th International Conference on Human Herpesviruses‐6 and ‐7 (HHV‐6A, ‐6B, and HHV‐7). Issue 4 (4th January 2018) - Komaroff, Anthony L.; Boeckh, Michael; Eliason, Eva; Phan, Tuan; Kaufer, Benedikt B.
Abstract : The 10th International Conference on Human herpesviruses‐6 and ‐7 (HHV‐6A, HHV‐6B, and HHV‐7) was held at the Freie Universität, Berlin, Germany from July 23‐26, 2017. It attracted more than 130 basic, translational and clinical scientists from 19 countries. Important new information was presented regarding: the biology of HHV‐6A and ‐6B; the biology and epidemiology of inherited chromosomally integrated HHV‐6A and ‐6B; improved diagnostic tests; animal models for and animal viruses with similarities to HHV‐6A, ‐6B, and ‐7; established and possible disease associations; and new treatment strategies. Here, we summarize work presented at the meeting that is of particular interest.